Composition studies as a creative art : teaching, writing, scholarship, administration - Bloom, Lynn Z., 1934- (Logan, Utah : Utah State University Press, 1998)
Bloom gathers twenty of her most recent essays (some previously unpublished) on critical issues in teaching writing. She addresses matters of philosophy and pedagogy, class and marginality and gender, and textual terror transformed to textual power. Yet the body of her work and this representative collection of it remains centered, coherent, and personal. This work focuses on the creative dynamics that arise from the interrelation of writing, teaching writing, and ways of reading--and the scholarship and administrative issues engendered by it. To regard composition studies as a creative art is to engage in a process of intellectual or aesthetic free play, and then to translate the results of this play into serious work that yet retains the freedom and playfulness of its origins. The book is fueled by a mixture of faith in the fields that compose composition studies, hope that efforts of composition teachers can make a difference, and a sense of community in its broadest meaning. Included are Bloom's well-known essays "Teaching College English as a Woman," "Freshman Composition as a Middle Class Enterprise," and many more recent works, equally provocative and insightful
Finding family, finding a voice : a writing teacher teaches writing teachers -- Teaching my class -- Freshman composition as a middle class enterprise -- Textual terror, textual power : teaching literature through writing literature -- American autobiography and the politics of genre -- Teaching college English as a woman -- Creative nonfiction, is there any other kind? -- Reading, writing, teaching essays as jazz -- Why don't we write what we teach? and publish it? -- Subverting the academic masterplot -- Coming of age in the field that had no name -- Anxious writers in context -- I write for myself and strangers : private diaries as public documents -- Making essay connections : editing readers for first-year writers -- The importance of external reviews in composition studies -- Want a writing director -- Why I (used to) hate to give grades -- Initiation rites, initiation rights / with Thomas Recchio -- Making difference : writing program administration as a creative process -- Bloom's laws.
Includes bibliographical references (pages 248-259) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
English.
Keywords: English language -- Rhetoric -- Study and teaching; English language -- Composition and exercises; Creative writing -- Study and teaching; Anglais (Langue) -- Composition et exercices; Création littéraire -- Étude et enseignement; LANGUAGE ARTS & DISCIPLINES -- Rhetoric; REFERENCE -- Writing Skills; LANGUAGE ARTS & DISCIPLINES -- Composition & Creative Writing; LANGUAGE ARTS & DISCIPLINES -- General; Creative writing -- Study and teaching; English language -- Composition and exercises; English language -- Rhetoric -- Study and teaching; Electronic book